Recession flow prediction in gauged and ungauged basins by just considering past discharge information. Issue 1 (2nd January 2020) - Reddyvaraprasad, Chillara; Patnaik, Swagat; Biswal, Basudev
ABSTRACT: Two contrasting methods have been proposed recently to predict the recession flow coefficient using past discharge information only. This study proposes a new method that attempts to obtain past discharge information that is minimally influenced by non-subsurface storage-controlled flows. The existing and new methods were tested using data from 324 US Geological Survey basins, and the new method was found to be superior to both existing methods in 265 basins. Furthermore, this study for the first time used past discharge-derived coefficients to predict recession discharge. The model performance was found to be satisfactory (NSE > 0.5) in 244 basins. Our results also show that the new framework may be useful in certain regions for predicting recession discharge in totally ungauged basins using past discharge information from nearby gauged basins. Overall, this study advances the idea that recession discharge can be predicted by just using past discharge data.